Environmental cleanup at Navy facilities : adaptive site management (National Academies Press, 2003)
The number of hazardous waste sites across the United States has grown to approximately 217,000, with billions of cubic yards of soil, sediment, and groundwater plumes requiring remediation. Sites contaminated with recalcitrant contaminants or with complex hydrogeological features have proved to be a significant challenge to cleanup on every level--technologically, financially, legally, and sociopolitically. Like many federal agencies, the Navy is a responsible party with a large liability in hazardous waste sites. "Environmental Cleanup at Navy Facilities applies the concepts of adaptive management to complex, high-risk hazardous waste sites that are typical of the military, EPA, and other responsible parties. The report suggests ways to make forward progress at sites with recalcitrant contamination that have stalled prior to meeting cleanup goals. This encompasses more rigorous data collection and analysis, consideration of alternative treatment technologies, and comprehensive long-term stewardship